ARE ISLAMIC INDICES A VIABLE INVESTMENT AVENUE? A FACTOR-BASED ANALYSIS OF THE US MARKET - Al-Harbi , Ahmad T. (International Journal of Islamic Banking and Finance Research, 2025)
This study is motivated by the ongoing debate on whether Shariah-compliant investment screening constrains portfolio performance relative to conventional benchmarks, particularly in developed capital markets such as the United States. Although Islamic equity indices have gained prominence, empirical evidence on their risk-adjusted performance remains mixed and often sensitive to market conditions and methodological choices. The study investigates whether Islamic indices constitute a viable investment avenue by empirically comparing the performance of a Shariah-compliant exchange-traded fund (SPUS) with its conventional counterpart (SPY) in the US equity market. This study employs monthly return data for both ETFs covering the period from January 2020 to December 2023, along with market, size, value, and momentum factors obtained from the F. French Data Library. Risk-adjusted performance is evaluated using Sharpe, Treynor, Information, and M-squared ratios, while return attribution is examined using the Carhart four-factor model supported by sub-period and bootstrap robustness analyses. The results show that SPUS generated a higher annualized return of 16.31% compared to 13.37% for SPY, with comparable volatility levels, and achieved a higher Sharpe ratio (0.7238 versus 0.5829). However, the estimated alpha of 0.0028 is statistically insignificant (p-value = 0.1048), and the 95% bootstrap confidence interval includes zero. The findings of this study suggest that the observed outperformance of the Islamic index is quantitatively explained by its significant exposure to large-cap growth factors, rather than by a statistically significant abnormal return. JEL Classification Codes: G11, G12, G15, Z12.